Brain ventricular volume changes in schizophrenia. A narrative review. (10th August 2021) - Svancer, Patrik; Spaniel, Filip
Highlights: Enlargement of brain ventricles represents one of the most robust findings in schizophrenia. Exact onset and dynamics of ventricular changes are still elusive. Morphological changes in schizophrenia are attributed to neurodevelopmental and/or neurodegenerative causes. Ventricular enlargement might be a marker of neurodegeneration in a subset of schizophrenia patients. Abstract: Brain ventricles are among the most studied structures in psychotic illness. In our mini-review we present available evidence on brain ventricle changes during the course of schizophrenia, from high-risk subjects and the first episode of schizophrenia to patients with chronic schizophrenia. We present current findings on the relationship between ventricle changes and level of psychopathology. The potential pathophysiological background of ventricle changes is also discussed. Understanding the dynamics of brain ventricle changes could resolve long-standing questions on the proportion of neurodegenerative and neurodevelopmental processes in the pathophysiology of schizophrenia.